A Case Study Of E-Supply Chain & Business Process Reengineering Of A Semiconductor Company In Malaysia - PPKAW, Pusat Pengajian Kejuruteraan Awam (2011)
e-business involvement in supply chain have created a new e-supply chain(e-SC) in firms locally and globally.